High-throughput screening of PLGA thin films utilizing hydrophobic fluorescent dyes for hydrophobic drug compounds - Steele, Terry W. J. (2017)
Hydrophobic, antirestenotic drugs such as paclitaxel (PCTX) and rapamycin are often incorporated into thin film coatings for local delivery using implantable medical devices and polymers such as drug-eluting stents and balloons. Selecting the optimum coating formulation through screening the release profile of these drugs in thin films is time consuming and labor intensive. We describe here a high-throughput assay utilizing three model hydrophobic fluorescent compounds: fluorescein diacetate (FDAc), coumarin-6, and rhodamine 6G that were incorporated into poly(d,l-lactide-co-glycolide) (PLGA) and PLGA–polyethylene glycol films. Raman microscopy determined the hydrophobic fluorescent dye distribution within the PLGA thin films in comparison with that of PCTX. Their subsequent release was screened in a high-throughput assay and directly compared with HPLC quantification of PCTX release. It was observed that PCTX controlled-release kinetics could be mimicked by a hydrophobic dye that had similar octanol–water partition coefficient values and homogeneous dissolution in a PLGA matrix as the drug. In particular, FDAc was found to be the optimal hydrophobic dye at modeling the burst release as well as the total amount of PCTX released over a period of 30 days.